Application of the multi-standard methodology for calculating 1H NMR chemical shifts - Sarotti, Ariel Marcelo (2012)
Gauge including atomic orbitals (GIAO)1H NMR chemical shift calculations have been performed for 66 organic compounds at 72 di fferent levels of theory using the multi-standard approach (MSTD) previously developed for 13C NMR. This straightforward computational technique involves the combination of methanol and benzene as standards. The studied methodology has been shown to predict 1H NMR chemical shifts efficiently at different levels of theory.